2021
DOI: 10.2147/pgpm.s285144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP2C19 Gene Polymorphisms in Patients with Acid Peptic Disorders Treated with Esomeprazole

Abstract: Background CYP2C19 is a highly polymorphic gene that encodes an enzyme with the same name and whose function is associated with the metabolism of many important drugs, such as proton pump inhibitors (such as esomeprazole, which is used for the treatment of acid peptic disease). Genetic variants in CYP2C19 alter protein function and affect drug metabolism. This study aims to genotypically and phenotypically characterize the genetic variants in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(47 reference statements)
0
3
0
Order By: Relevance
“… 19 In a small study involving 12 patients, it was observed that after a 14-day course of esomeprazole treatment, the duration of pH > 4 recorded in 24-hour monitoring did not differ significantly across different phenotypes. 4 Conversely, another study demonstrated that CYP2C19 UMs displayed a statistically significant increase in duration during which the pH remained below 4. 20 For future studies, it would be interesting to compare DeMeester scores among different metabolizer groups while on PPI therapy using a larger patient population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 19 In a small study involving 12 patients, it was observed that after a 14-day course of esomeprazole treatment, the duration of pH > 4 recorded in 24-hour monitoring did not differ significantly across different phenotypes. 4 Conversely, another study demonstrated that CYP2C19 UMs displayed a statistically significant increase in duration during which the pH remained below 4. 20 For future studies, it would be interesting to compare DeMeester scores among different metabolizer groups while on PPI therapy using a larger patient population.…”
Section: Discussionmentioning
confidence: 97%
“… 3 Still, some variance exists among different PPIs: first-generation PPIs, including omeprazole and pantoprazole are mainly metabolized by CYP2C19 with secondary involvement of CYP3A4, while lansoprazole is primarily metabolized by both. 4–6 Second-generation PPIs, including rabeprazole and esomeprazole, are less dependent on CYP2C19 pathway. 5 , 6 Dexlansoprazole, another second-generation PPI, shares a similar metabolic pathway to lansoprazole.…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of scientific investigations 11,12 have compellingly illustrated that gene polymorphism exerts a substantial influence on the activity of metabolic enzymes. This leads to discrepancies in enzyme expression and function among individuals possessing different genotypes, thereby potentially instigating variations in drug absorption, distribution, and metabolism.…”
Section: Discussionmentioning
confidence: 99%